Determinantes del endeudamiento a largo plazo de las empresas del sector minero en el Perú 2005-2011 - Pazos Zavaleta, Luz Marina (2013)
The current research paper has as purpose to identify which are the mining companies’ determinants of long term indebtedness in Peru. Those companies were chosen according to its size, assets level, and profitability during the period of 2005 to 2011. In order to develop this study, a behavioral analysis of the mining sector in Peru has been made covering the indicated period; in the same way, evolution of each one of the variables with respect to the companies' indebtedness level was analysed. To that purpose, financial information from a sample of 18 mining companies listing in the Lima Stock Exchange was used. Finally, the relationship between the dependent and independent variable was empirically verified by using an econometric model as well as the data panel methodology. The research concludes that, the mining companies’ determinants of long term indebtedness in Peru in the period of 2005 to 2011, are the size, assets level, and profitability. For mining companies, the size and the level of assets positively influence on long term indebtedness; on the other hand, profitabilty influences in a negative way, which agrees with the theory that has been used in the development of the current study.